PENGARUH SIKAP BELAJAR TERHADAP PRESTASI BELAJAR SISWA DALAM MATA PELAJARAN AKUNTANSI DI SMK NASIONAL AL - HUDA PEKANBARU - Puspasari, Syarifah Nurlinda; ', Sumarno; ', RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study was to determine the effect of students' attitudes toward learning achievement in the subject of Accounting Class X1 National SMK Al-Huda Pekanbaru. The population in this study were all students of class XI, totaling 26 students who all be sampled in this study. Data used was primary data and secondary data, the data were analyzed descriptively and simple linear regression. The results showed that the attitude of learning to give a contribution of 34.2% on student achievement X1 class majoring in accounting at the National SMK Al-Huda Pekanbaru 2016-2017 school year.Keywords: Accounting Learning Achievement, Attitude Study